2006
DOI: 10.1002/ijc.21919
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of treatment outcome by cisplatin‐DNA adduct formation in patients with stage III/IV head and neck squamous cell carcinoma, treated by concurrent cisplatin‐radiation (RADPLAT)

Abstract: The purpose of our study was to test the predictive value of cisplatin-DNA adduct levels in head and neck squamous cell carcinoma (HNSCC) patients treated with cisplatin-radiation. Patients with advanced-stage HNSCC were treated within a randomized trial, investigating the optimal route of cisplatin administration, concurrently with radiation. Cisplatin was administered intra-arterially (IA, 150 mg/m 2 , with systemic rescue by sodium thiosulfate) or intravenously (IV, 100 mg/m 2 ). In a subgroup, adducts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…When expressed as a continuous variable, the levels of platinum-DNA adducts was not associated with PFS, OS, or the results of SLL in this cohort. In contrast, the level of platinum-DNA adducts in buccal cells was shown to be an independent predictor of better OS in NSCLC (20), and the level of platinum-DNA adducts in tumor tissue was shown to be an independent predictor of better PFS but not OS in HNSCC (21). A number of differences exist between these studies that likely contribute, at least in part, to the disparity in results, including the patient population (EOC versus NSCLC versus HNSCC), method for detecting platinum-DNA adducts Although tumor response was not an end point in the study reported herein, SLL was allowed when declared at the time of protocol enrollment and provided an opportunity to evaluate disease status in this population with optimally debulked stage III EOC.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…When expressed as a continuous variable, the levels of platinum-DNA adducts was not associated with PFS, OS, or the results of SLL in this cohort. In contrast, the level of platinum-DNA adducts in buccal cells was shown to be an independent predictor of better OS in NSCLC (20), and the level of platinum-DNA adducts in tumor tissue was shown to be an independent predictor of better PFS but not OS in HNSCC (21). A number of differences exist between these studies that likely contribute, at least in part, to the disparity in results, including the patient population (EOC versus NSCLC versus HNSCC), method for detecting platinum-DNA adducts Although tumor response was not an end point in the study reported herein, SLL was allowed when declared at the time of protocol enrollment and provided an opportunity to evaluate disease status in this population with optimally debulked stage III EOC.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies evaluated the relationship between platinum-DNA adducts in peripheral leukocytes and disease response but not PFS or OS in a variety of cancers including ovarian cancer (8)(9)(10)(11)(12)(13)(14)(16)(17)(18) or between platinum-DNA adducts in either buccal cells or tumor and disease response in a variety of cancers (19), OS in NSCLC (20), or with PFS and OS in HNSCC (21). In these studies, platinum-DNA adducts were assessed using an ELISA (8)(9)(10)(11)(12)14) atomic absorbance spectroscopy (12-14, 16, 17), inductively coupled plasma-mass spectroscopy (18), immunocytochemistry (19,20), or 32 P postlabeling (21). This study showed that the presence of platinum-DNA adducts in PBL 20 to 28 h after the first cycle of chemotherapy was associated with better OS, but not with PFS or the results of SLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a significantly better disease-free survival was reported for cisplatin-treated head and neck carcinoma patients with higher adduct levels (Hoebers et al, 2006). The feasibility of intraindividual dose escalation of cisplatin based on platinum-DNA adduct levels has been shown in two clinical trials in patients with head and neck cancer (Schellens et al, 2001) and non-small cell lung cancer (Schellens et al, 2003).…”
mentioning
confidence: 99%
“…5 More recently, Hoebers et al measured cisplatin adduct levels in patients with head and neck cancer receiving either IV or IA cisplatin. 6 Although the level of GG adduct formation was higher in the IA group, this was not statistically significant; however, there were only 5 patients in the IA group and 7 in the IV group. Furthermore, some of the subjects would have received a reduced amount of the total drug infused if they received a bilateral IA infusion.…”
mentioning
confidence: 76%